2017
DOI: 10.21037/atm.2017.07.36
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes of titanium modular femoral necks in total hip arthroplasty

Abstract: Background: Modular femoral necks present surgical and biomechanical advantages in total hip arthroplasty (THA), but their benefits remain controversial due to risks of corrosion and fracture at the additional junction. This study aimed to report 10-year survival and clinical outcomes of a titanium femoral stem with a titanium modular neck in consecutive series. Methods:The authors reviewed the records of 97 patients (99 THAs) using uncemented modular stem and ceramic-on-ceramic acetabular components. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…7–98.6). Collet et al, 38 in their series, registered a mean postoperative HHS of 93.6±8.2 at a mean follow-up of 9.4 years, which was greater than the results reported by several other authors. 26 , 30 , 33 The MAPS score summarized in Table 3 improved from an average preoperative score of 10 to a postoperative mean score of 17.5 (15–18).…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…7–98.6). Collet et al, 38 in their series, registered a mean postoperative HHS of 93.6±8.2 at a mean follow-up of 9.4 years, which was greater than the results reported by several other authors. 26 , 30 , 33 The MAPS score summarized in Table 3 improved from an average preoperative score of 10 to a postoperative mean score of 17.5 (15–18).…”
Section: Resultsmentioning
confidence: 50%
“…As described by different authors 5 , 10 , 38 the modularity was effective in restoring offset and leg length, and these confer stability with a good mid to long-term follow-up. Traina et al 49 reported that MN prostheses allow the restoration of femoral offset, abductors moment arm, leg length and joint kinematics especially in critical cases of THA, such as high-grade dysplasia.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In recent years, some studies have reported satisfactory results using dual modular stems in primary THAs [ 106 , 107 , 108 ]. Specific dual modular stems offer a better reconstruction of hips that deviate from standard anatomy when compared to a monoblock arthroplasty system with different offset options [ 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modular stems have been studied by many authors as they allow intraoperative adjustments of femoral neck anteversion, offset, and limb length to better restore muscle tensions and hip biomechanics (5)(6)(7)(8). In primary THA, several modular stems have been associated with corrosion or fracture at their junctions, though models made of titanium bodies and necks seem to obviate these problems, and grant satisfactory mid-term survival and excellent clinical outcomes at 10 years (9).…”
Section: Introductionmentioning
confidence: 99%